2022
DOI: 10.31393/morphology-journal-2022-28(3)-10
|View full text |Cite
|
Sign up to set email alerts
|

Shape of cerebral hemispheres: structural and spatial complexity. Quantitative analysis of skeletonized MR images

Abstract: For quantitative characterization of the complexity of the spatial configuration of anatomical structures, including cerebral hemispheres, fractal analysis is the most often used method, in addition to which, other methods of image analysis are quite promising, including quantitative analysis of skeletonized images. The purpose of the study was to determine the features of the structural and spatial complexity of the cerebral hemispheres shape using quantitative analysis of skeletonized magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, this value of fractal dimension was associated with parameters of the digital skeleton, which were larger in males than in females and decreased with age: these included branches, junctions, junction voxels, slab voxels, and triple points. In our previous study (Maryenko and Stepanenko, 2022b), it was found that the mentioned quantitative parameters of digital skeletons had positive correlation relationships with the area of brain sections. Thus, a decrease in the silhouette area during skeletonizing will lead to the formation of a skeleton with fewer internal branches and their connections, resulting in a decrease in fractal dimension values.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, this value of fractal dimension was associated with parameters of the digital skeleton, which were larger in males than in females and decreased with age: these included branches, junctions, junction voxels, slab voxels, and triple points. In our previous study (Maryenko and Stepanenko, 2022b), it was found that the mentioned quantitative parameters of digital skeletons had positive correlation relationships with the area of brain sections. Thus, a decrease in the silhouette area during skeletonizing will lead to the formation of a skeleton with fewer internal branches and their connections, resulting in a decrease in fractal dimension values.…”
Section: Discussionmentioning
confidence: 84%
“…This method of image analysis is primarily used in studies of neurons and their dendritic trees (Li et al, 2019;Jiang et al, 2020). In our previous works, we conducted a fractal analysis of the contour (Maryenko and Stepanenko, 2023) and digital skeletons of the cerebral hemispheres (Maryenko and Stepanenko, 2022a) and, for the first time, attempted to perform quantitative analysis of skeletonized images of the cerebral hemispheres (Maryenko and Stepanenko, 2022b). In this study, our aim was to compare the features of the structural complexity of the cerebral hemispheres in men and women using fractal analysis of outlined and skeletonized images, as well as quantitative analysis of digital skeletons of the cerebral hemispheres.…”
Section: Introductionmentioning
confidence: 99%